Kinesin-1 interacts with Bucky ball to form germ cells and is required to pattern the zebrafish body axis - Campbell, Philip D. (Development, 2015)
In animals, specification of the primordial germ cells (PGCs), the stem cells of the germ line, is required to transmit genetic information from one generation to the next. Bucky ball (Buc) is essential for germ plasm (GP) assembly in oocytes, and its overexpression results in excess PGCs in zebrafish embryos. However, the mechanistic basis for the excess PGCs in response to Buc overexpression, and whether endogenous Buc functions during embryogenesis, are unknown. Here, we show that endogenous Buc, like GP and overexpressed Buc-GFP, accumulates at embryonic cleavage furrows. Furthermore, we show that the maternally expressed zebrafish Kinesin-1 Kif5Ba is a binding partner of Buc and that maternal kif5Ba (Mkif5Ba) plays an essential role in germline specification in vivo. Specifically, Mkif5Ba is required to recruit GP to cleavage furrows and thereby specifies PGCs. Moreover, Mkif5Ba is required to enrich Buc at cleavage furrows and for the ability of Buc to promote excess PGCs, providing mechanistic insight into how Buc functions to assemble embryonic GP. In addition, we show that Mkif5Ba is also essential for dorsoventral (DV) patterning. Specifically, Mkif5Ba promotes formation of the parallel vegetal microtubule array required to asymmetrically position dorsal determinants (DDs) towards the prospective dorsal side. Interestingly, whereas Syntabulin and wnt8a translocation depend on kif5Ba, grip2a translocation does not, providing evidence for two distinct mechanisms by which DDs might be asymmetrically distributed. These studies identify essential roles for maternal Kif5Ba in PGC specification and DV patterning, and provide mechanistic insight into Buc functions during early embryogenesis.